2021
DOI: 10.1099/mic.0.000962
|View full text |Cite
|
Sign up to set email alerts
|

A novel hemA mutation is responsible for a small-colony-variant phenotype in Escherichia coli

Abstract: We identified a small colony variant (SCV) of an amoxicillin/clavulanic acid-resistant derivative of a clinical isolate of Escherichia coli from Malawi, which was selected for in vitro in a subinhibitory concentration of gentamicin. The SCV was auxotrophic for hemin and had impaired biofilm formation compared to the ancestral isolates. A single novel nucleotide polymorphism (SNP) in hemA, which encodes a glutamyl-tRNA reduc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In addition to the 260 clones that were found to have decreased survival after 6 days of levofloxacin exposure in the previous study ( Wang et al, 2015 ), we identified seven clones with deficiency in persister formation that had a transposon insertion between nucleotides 854 and 855 of hemA ( Figure 1A ; Supplementary Figure S1 ). And mutant in hemA resulting in SCV has been reported before ( Curtis et al, 2016 ; Hubbard et al, 2021 ).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to the 260 clones that were found to have decreased survival after 6 days of levofloxacin exposure in the previous study ( Wang et al, 2015 ), we identified seven clones with deficiency in persister formation that had a transposon insertion between nucleotides 854 and 855 of hemA ( Figure 1A ; Supplementary Figure S1 ). And mutant in hemA resulting in SCV has been reported before ( Curtis et al, 2016 ; Hubbard et al, 2021 ).…”
Section: Resultsmentioning
confidence: 85%
“…To examine whether the heme biosynthesis pathway is associated with persister formation, we knocked out hemA and the downstream hemB gene by allelic gene replacement from S. aureus USA500 wildtype ( Figure 1B ). When either of these two genes was knocked out, the strains displayed a typical SCV phenotype ( Figures 1C , D ; Jonsson et al, 2003 ; Garcia et al, 2012 ; Proctor et al, 2014 ; Hubbard et al, 2021 ). After complementing the knockout genes separately, the phenotype was both reverted and the reversion was complete ( Figures 1E , F ).…”
Section: Resultsmentioning
confidence: 99%
“…Here the group isolate an SCV from a clinical isolate of E. coli from Malawi by selecting for isolates that are more tolerant to the aminoglycoside gentamicin [20]. By genome sequencing the resistant isolate, they identify a single-nucleotide polymorphism (SNP) in the hemA gene, which results in the Phe to Leu alternation in the resulting protein that likely reduces function.…”
Section: Full-textmentioning
confidence: 99%
“…They were able to recapitulate the phenotypes of Gotz’s group of reduced colony size (the small-colony variant, SCV) and also a growth defect at atmospheric CO 2 levels that could be complemented by 5 % CO 2 . A known phenotype of the SCVs is reduced membrane potential, which they also observed, seeing similar levels to a hemB mutant, which reminded me of a paper we published last year by Alastair Hubbard ( @dralhubb ) and colleagues on a novel hemA mutant that also induces SCV formation by a similar mechanism [ 7 ]. So why is the presence of MpsB making the cells more sensitive to serum?…”
Section: Full-textmentioning
confidence: 81%